Botryane terpenoids produced by Nemania bipapillata, an endophytic fungus isolated from red alga Asparagopsis taxiformis - Falkenbergia stage - Medina, Rebeca P. [UNESP]; Araujo, Angela R. [UNESP]; Batista, João M.; Cardoso, Carmen L.; Seidl, Cláudia; Vilela, Adriana F. L.; Domingos, Helori V.; Costa-Lotufo, Leticia V.; Andersen, Raymond J.; Silva, Dulce H. S. [UNESP] (Springer Nature, 2019)
A chemical study of the EtOAc extract of Nemania bipapillata (AT-05), an endophytic fungus isolated from the marine red alga Asparagopsis taxiformis - Falkenbergia stage, led to the isolation of five new botryane sesquiterpenes, including the diastereomeric pair (+)-(2R,4S,5R,8S)-(1) and (+)-(2R,4R,5R,8S)-4-deacetyl-5-hydroxy-botryenalol (2), (+)-(2R,4S,5R,8R)-4-deacetyl-botryenalol (3), one pair of diastereomeric botryane norsesquiterpenes bearing an unprecedented degraded carbon skeleton, (+)-(2R,4R,8R)-(4) and (+)-(2R,4S,8S)-(5), which were named nemenonediol A and nemenonediol B, respectively, in addition to the known 4β-acetoxy-9β,10β,15α-trihydroxyprobotrydial (6). Their structures were elucidated using 1D and 2D NMR, HRESIMS and comparison with literature data of similar known compounds. The absolute configurations of 2, 3 and 4 were deduced by comparison of experimental and calculated electronic circular dichroism (ECD) spectra, while those of 1 and 5 were assigned from vibrational circular dichroism (VCD) data. Compound 4 weakly inhibited acetylcholinesterase, whereas compound 1 inhibited both acetylcholinesterase and butyrylcholinesterase. Compounds 1, 3, 5 and 6 were tested against two carcinoma cell lines (MCF-7 and HCT-116), but showed no significant citotoxicity at tested concentrations (IC50 > 50 µM).